Impact of severe mitral annular calcification on mitral regurgitation after transcatheter aortic valve implantation. (4th February 2022) - Calvao, J; Costa, C; Amador, A; Pinto, R; Carvalho, M; Proenca, T; Marques, C; Cabrita, A; Grilo, P; Resende, C; Torres, S; Sousa, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Transcatheter aortic valve implantation (TAVI) has become the standard of care treatment in patients with severe aortic stenosis who are at intermediate or high risk for surgical aortic valve replacement. Mitral annular calcification (MAC) is frequent in patients with aortic stenosis, and its presence is associated with increased cardiovascular morbidity and mortality. Not infrequently, it is associated with significant morphologic and functional abnormalities of the mitral valve apparatus. Purpose:  The aim of this work is to evaluate the relationship between severe MAC and the presence and development of significant mitral regurgitation after TAVI. Methods:  We retrospectively analyzed all patients who underwent TAVI at a tertiary center from October 2014 to November 2019. Clinical, echocardiographic and procedure-related data were collected until a follow-up of 6 months. Statistical analysis was conducted on IBM SPSS® Statistics software. Descriptive statistics were calculated for all variables. Sample T-test, Chi-square and Wilcoxon sign test were used. A p-value < 0.05 was considered significant. The presence and severity of MAC was defined according to echocardiographic data. Severe MAC was defined by the presence of calcification of more than half of the mitral annular circumference. Results:  A total of 343 patients were enrolled in the study. The mean age of the population was 80 ± 8 years, 45% were male. Mean functional area was 0.75 ± 0.18 cm2, mean transvalvular pressure gradient was 48 ± 15 mmHg and the mean left ventricular ejection fraction (LVEF) was 54 ± 14%.  MAC was detected in 231 (67%) patients. In 44 (19%) of these patients, MAC was graded as severe. Patients with severe MAC tended to have higher prevalence of moderate (27.3 vs 20.4%, p = 0.30) as well as severe (4.5 vs 1.8%, p = 0.24) mitral regurgitation at baseline. After TAVI, the prevalence of moderate mitral regurgitation at 6 months was similar between both groups (22.5 vs 20.4%, p = 0.76). Although not reaching statistical significance, patients with severe MAC had higher prevalence of severe mitral regurgitation at 6 months post-procedure (12.2 VS 5.0%, p = 0.07) as well as higher incidence of worsening of mitral regurgitation (34.2 vs 23.7%, p = 0.16). The proportion of patients that had improvement (13.2 vs 15.0%, p = 0.76) or no change (52.6 vs 61.3%, p = 0.31) in the degree of mitral regurgitation was similar in both groups.  Conclusion:  The presence of severe MAC at baseline echocardiography in patients undergoing TAVI may be associated with worsening of mitral regurgitation after the procedure. These patients tend to have higher prevalence of severe mitral regurgitation post-TAVI. Further studies are needed in order to further elucidate this association.